The "side‐BASE technique": Combined side branch anchor balloon and balloon assisted sub‐intimal entry to resolve ambiguous proximal cap chronic total occlusions. Issue 1 (20th December 2017) - Roy, James; Hill, Jonathan; Spratt, James C.
Abstract: Failure to penetrate the proximal cap or cross with equipment remains the most frequent cause of procedural failure in CTO PCI. In the "BASE" technique concerns were raised over the risk of proximal side branch loss. We here describe the evolution of this technique and highlight examples where the sub‐intimal space was accessed proximal to the occlusion by using the side branch. This technique can be of use both in resolving proximal cap ambiguity and also in cases where there is difficulty crossing a resistant proximal cap.